Kesiapan Guru dalam Pembelajaran Daring di SD Lingkungan DAS Desa Pahandut - Roso Sugiyanto; Laila Rahmawati; Maneka Ciciana; Carolina Fransiska; Sri Fathonah Ayuningrum (FKIP Universitas Palangka Raya, 2021)
Social distance forces all sectors to innovate, one of which is in the world of education. Where the government asks schools to implement distance learning using online learning. Online learning activities are much more difficult to do than face-to-face learning because they have to utilize several technologies in their application and are able to use appropriate models, strategies, media, teaching materials and assessments. This situation is a challenge, especially for teachers. Therefore, optimal readiness is needed in the implementation of online learning, especially in elementary schools located in the watershed (Watershed Area). This study uses a descriptive qualitative approach that aims to describe and describe the readiness of teachers in online learning. The research subjects were 24 teachers from three schools using random sampling technique. The results obtained from the implementation of learning from these three schools are that the preparations made by teachers are still not optimal, due to several factors, namely the community environment and parents / guardians of students who are less supportive, facilities and infrastructure in schools that are still lacking and human resources are inadequate. there are some schools that have not been able to carry out online learning activities well. So that later it is hoped that there will be improvements and problem solving solutions from the less than optimal preparation for the implementation of online learning in several schools.